A rocket-like encapsulation and delivery system with two-stage booster layers : pH-responsive poly(methacrylic acid)/poly(ethylene glycol) complex-coated hollow silica vesicles - Liu, Ye (2013)
Rocket-like vesicles formed are composed of poly(acrylic aicd) (PMAA )/poly(ethylene glycol) (PEG) complex coated hollow silica spheres, and the structure and composition of the vesicles are characterized using TGA, 1H NMR, FTIR, and TEM. Although only one-third of EG units of PEG brushes grafted to hollow silica spheres form the complex with PMAA via hydrogen bonding, the first “booster” layer composed of PMAA/PEG complex can provide secure encapsulation of model compound calcein blue under an acidic condition. The second “booster” layer composed of PEG brushes can be formed by changing acidic pH to 7.4 through the disassociation of the PMAA/PEG complex. A higher molecular weight PMAA exhibits a faster disassembly due to the formation of a looser PMAA/PEG complex on the surfaces of hollow silica spheres.